Improving system static security via optimal placement of static var compensator using Multi Verse Optimizer (MVO) - Siti Nur Hazirah, Asmadi; Nor Rul Hasma, Abdullah; Shanono, Ibrahim Haruna; Mahfuzah, Mustafa; Rosdiyana, Samad (Institution of Engineering and Technology, 2022)
Numerous Flexible AC Transmission System (FACTS) devices have been installed in transmission networks in recent years. Due to energy demand rising, so does load consumption, resulting in increased power losses. This paper aims Multi Verse Optimizer (MVO) for transmission loss minimization and to optimize the location and sizing of Static VAR Compensator (SVC) to be installed. Multi Verse Optimizer (MVO) approach is suggested as a solution to improve system static security and optimize location sizing via optimal placement of SVC then validate it on standard IEEE 30-bus Reliability Test System (RTS) system. The objective function of this research is to minimize power loss using MVO by determining the location and sizing of SVC to be installed in the system. The obtained results demonstrate that installing SVCs in the system can aid in minimizing losses in weak and secure buses. The expected result shows that using MVO can determine the optimal parameters and reduce losses.